Pediatric macular hole repair with amniotic membrane graft in a patient with leukemia - Vahid Ownagh; Nita G. Valikodath; Lejla Vajzovic (American Journal of Ophthalmology Case Reports, 2025)
Purpose: Idiopathic macular holes are rare in children. The optimal management and surgical technique have not been fully investigated in chronic pediatric macular holes. Observations: Here we report a pediatric patient with leukemia who presented with non-clearing vitreous hemorrhage and intraoperative identification of a full thickness macular hole. After pars plana vitrectomy and internal limiting membrane peeling, a human amniotic membrane transplant (AMT) was fashioned and tucked under the retina at the edge of macular hole. Silicone oil was used to provide sufficient tamponade to the graft as the patient lived at high elevation. At follow up the graft was properly incorporated in the retina with successful anatomic closure of the macular hole without graft displacement, intraocular inflammation, or retinal detachment. One month after surgery visual acuity was 3/100 with subsequent improvement to 20/70 at final follow up. The graft remained well integrated in the retina after silicone oil removal. Optical coherence tomography demonstrated restoration of foveal contour with disruption in outer retinal layers. Conclusion and importance: Unlike idiopathic senile macular holes, application of AMT for idiopathic macular holes in children has not been investigated. Our case suggests amniotic membrane graft as an adjunctive tool in management of pediatric macular holes.